2(x-4)+3=(2x+5)

Simple and best practice solution for 2(x-4)+3=(2x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-4)+3=(2x+5) equation:


Simplifying
2(x + -4) + 3 = (2x + 5)

Reorder the terms:
2(-4 + x) + 3 = (2x + 5)
(-4 * 2 + x * 2) + 3 = (2x + 5)
(-8 + 2x) + 3 = (2x + 5)

Reorder the terms:
-8 + 3 + 2x = (2x + 5)

Combine like terms: -8 + 3 = -5
-5 + 2x = (2x + 5)

Reorder the terms:
-5 + 2x = (5 + 2x)

Remove parenthesis around (5 + 2x)
-5 + 2x = 5 + 2x

Add '-2x' to each side of the equation.
-5 + 2x + -2x = 5 + 2x + -2x

Combine like terms: 2x + -2x = 0
-5 + 0 = 5 + 2x + -2x
-5 = 5 + 2x + -2x

Combine like terms: 2x + -2x = 0
-5 = 5 + 0
-5 = 5

Solving
-5 = 5

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 95+d=100 | | 2(x-7)+3x=2x-8 | | 95+d= | | 3(-6-1x)=-30 | | 3(2.5+-0.5y)-3y=3 | | 3+3x+1x=23 | | 6x^6-5x^3-1=0 | | 3x-8-3x-2=6 | | 6x+9+4x=19 | | 14f=14 | | 62-d=12 | | 1-7x+3x=-31 | | 66=22m | | 15b=225 | | e=mcqeur | | 4(9-2x)=4 | | -6x+5+3x=26 | | 77-a=12 | | 5y^2-8y=3 | | 4(-2x+5)=-26 | | (x*4)+6=18 | | 20x^3+6x^2-2x+1=0 | | 2(3+2x)=-26 | | -6(2.4+0.4y)-2y=-14 | | X^2-2kx+3k+2=0 | | -6(2.4+-0.4y)-2y=-14 | | (x-8)(x-3)=30 | | .75(20+6y)-.5(18-9y)= | | N+N=N(n) | | Z^2-z+1-i=0 | | 5x-10y-2=0 | | 7m+5=21-3m |

Equations solver categories